Calculation Model to Predict the Static Armor Layer Size Distribution After the Reconstruction of a Gravel River Bed - Wang, Qiang; Li, Like; Li, Xinjie; Wang, Yuanjian; Nie, Ruihua (Frontiers in Earth Science, 2021)
The size distribution of the armor layer in mountain rivers is an important factor affecting the stability of the river bed. However, there are relatively few studies on the prediction of the armor layer size distribution in the reconstruction process after the instability of the previous static armor layer. In response to the above challenges, this paper takes the incipient probability of sediment particles as the starting point, and comprehensively considers the coupling relationship between the initial bed materials, the bed structure, the armor ratio and flow intensity, a simple calculation model for predicting the static armor layer size distribution after the reconstruction of gravel-river bed is established. This paper introduces the concept of the critical incipient particle size , and considered that the sediment particles smaller than will incipient relatively easy, and the probability of being washed out is greater, while the incipient probability of sediment particles larger than (this part of the large-particle sediment includes not only the original particles on the bed surface, but also the large sediment particles exposed by the erosion of the bed subsurface) is relatively small. At the same time, this model also uses the armor ratio to reflect the bed surface structure impact. This paper cites data from five sets of laboratory flume experiments to verify the calculation model, and the experimental result shows that the calculation results of the model are in good agreement with the experimental measured data, especially in predicting the median diameter of the static armor layer. Our calculation model provides certain theoretical guidance for the study of mountain river bed stability and earthquake prevention and disaster reduction.